Study of Visual Meaning of Ornaments of Grave People of Minahasa District, North Sulawesi Province - Abdussamad, Cahya Pradipta; Kasmana, Kankan (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
This study aims to examine the meaning of the Waruga tomb ornament in North Sulawesi, precisely in Minahasa Regency. Waruga graves are tombs used to lay bodies as a belief of the people of North Sulawesi, especially the Minahasa tribe. The result of this research is to explain the visual meaning of the waruga tomb ornament. The approach used in this research is a qualitative descriptive approach, which means that the researcher collects data related to the graves of waruga, either in the form of books or materials related to the object under study, namely the waruga grave. The data collection technique is done through observation, interview, documentation study and document study. So that the conclusion of this study is that there is a meaning contained in the waruga tomb ornament, one of which is the meaning of the animal found in the grave which symbolizes the body that is inhaling semesa is a hunter and another meaning is that the person buried in the waruga grave is adjusted to work, drajat and rank during his lifetime. The waruga grave has been the grave or the main grave of the Minahasa tribe since ancient times until now, in one waruga grave there can be several people in the waruga grave according to the agreement of the family or elders in the North Sulawesi area, especially in the Minahasa land.